Spain : memorandum of interview / Walter Citrine... Senor del Vayo - Alvarez del Vayo, Julio, 1891-; Citrine, Walter, 1887-1983
016b-0045-001 PRIVATE & CONFIDENTIAL. MEMORANDUM OF INTERVIEW. Date 12th October, 1937. Time 10.30. to Reference WMC/FP/55 Present Sir Walter Citrine, Senor del Vayo, Mr. Gillies. SUBJECT. SPAIN. On Tuesday, the 12th October, at 10.30 a.m. Mr. del Vayo called by arrangement, when I explained to him, in the presence of Mr. Gillies, what had taken place at the interview at the Foreign Office. Mr. del Vayo agreed that the threat to open the French frontier had lost some of its force, and that the French should have acted some time ago. Mr. del Vayo said that he had already seen Mr. Attlee, and that he, del Vayo, would be returning to Paris in a few days, when he would again make representations to the French. I should add that I informed Mr. del Vayo yesterday about the breach of confidence that had taken place arising from my discussion with him and Senor [Negrau] Negrin at Geneva. I said that the report which had appeared in the "Daily Worker" of private conversations which I had had with Mr. Eden, although inaccurate in some particulars, must have been disclosed either by members of the Spanish delegation or by my colleagues. I had spoken to Longuet and de Brouckère, neither of whom had disclosed the information. Mr. del Vayo promised that he would enquire into the breach which, as I pointed out, came to be published through the same man, Pitcairn, the correspondent of the "Daily Worker", who had obtained admission by using Spanish delegates' credentials at the Joint Conference of the L.S.I. and the I.F.T.U. in London on the 11th March, 1937. 292/946/16b/49